2021
DOI: 10.1002/bit.27818
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles enhance the formation of seven major classes of natural products in native and metabolically engineered actinobacteria through accelerated morphological development

Abstract: Actinobacteria provide a rich spectrum of bioactive natural products and therefore display an invaluable source towards commercially valuable pharmaceuticals and agrochemicals. Here, we studied the use of inorganic talc microparticles (hydrous magnesium silicate, 3MgO•4SiO 2 •H 2 O, 10 µm) as a general supplement to enhance natural product formation in this important class of bacteria. Added to cultures of recombinant Streptomyces lividans, talc enhanced production of the macrocyclic peptide antibiotic bottrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 97 publications
1
22
0
Order By: Relevance
“…6b ). It should be noted that Kuhl et al ( 2021 ) applied a different medium, a different type of microparticles (talc), and, finally, cultivated S. rimosus under the conditions that were not equivalent to the ones applied here. It proves once again that the application of microparticles to enhance product titers should not be perceived as a ready-to-use solution but rather as a promising basis for further process optimization efforts, as was mentioned above with regard to lovastatin formation.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…6b ). It should be noted that Kuhl et al ( 2021 ) applied a different medium, a different type of microparticles (talc), and, finally, cultivated S. rimosus under the conditions that were not equivalent to the ones applied here. It proves once again that the application of microparticles to enhance product titers should not be perceived as a ready-to-use solution but rather as a promising basis for further process optimization efforts, as was mentioned above with regard to lovastatin formation.…”
Section: Discussionmentioning
confidence: 82%
“…One of the key factors to consider is the concentration of microparticles. It was shown in the same work of Kuhl et al ( 2021 ) that the presence of talc can lead either to the increase or decrease of oxytetracycline levels depending on its concentration in the medium. In many other studies focused on MPEC, the concentration of microparticles was found to be an important factor in the context of stimulating the production of metabolites and enzymes (Antecka et al 2016b ; Coban and Demirci 2016 ; Driouch et al 2010a , 2012 ; Kaup et al 2008 ; Gonciarz and Bizukojc 2014 ; Yatmaz et al 2016 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…For example, talc could be one of the preferable microparticle owing to its price in the range of 10 EUR cents per kg. Moreover, it could be evaluated in feed additives and fertilizers by co-harvested with biomass after fermentation process [77].…”
Section: Polysaccharidesmentioning
confidence: 99%
“…The improvement of biotechnological potential of S. albus J1074 was an important direction of studies, in the course of which new derivatives of this strain, plasmids for the expression of global regulators of the secondary metabolism were constructed, and different cultivation techniques providing a maximal productivity of this platform were worked out (Lopatniuk et al, 2017;Gummerlich et al, 2021;Kuhl et al, 2021). The selection of highly productive variants among streptomycin-resistant (Str R ) Streptomyces mutants is one of the historically first approaches to obtaining overproducers of antibiotics; most frequently, such mutations occur in the rpsL gene encoding the ribosomal protein S12 (Shima et al, 1996).…”
Section: Introductionmentioning
confidence: 99%